Pharmacology and intraocular pressure relationship of topical and systemic paracetamol in the adult New Zealand White Rabbit Eye - Anderson, Sean Glen (Stellenbosch : Stellenbosch University, 2022)
Thesis (MSc)--Stellenbosch University, 2022.